Hierarchy of the Peruvian legal system - Furnish, Dale Beck (1972)
This paper analyzes the Peruvian legal system with special emphasis on their normative hierarchy. In this way, quoting Hans Kelsen, the author mentions the three main classes of norms present in our legal system: i) the Political Constitution; ii) legislation; and iii) administrative acts. Regarding them, the author analyzes their content and also criticizes the influence of the political context in their development. Likewise, he delves into the problems noted with respect to constitutional supremacy and the mechanisms developed to act against the incompatibility of the norms and the Constitution: judicial review, habeas corpus and the provisions of the Organic Law of the Judiciary. Finally, the author analyzes the legislative powers of the Executive Branch and the political framework that influenced their scope.